Real Time Detection of R – Peak in QRS Complex of ECG using Microcontroller - Santipriya N; Venkateswara Rao M; Arun V; R Karthik (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Real-time detection of R peaks in QRS complex of ECG signal is the first step in the processing of ECG waveform. Based on this, various other ECG parameters can be extracted. These parameters provide substantial information about various heart diseases. In this paper, we are proposing a method to detect R – peaks of ECG signal dynamically. The most prominent role in the R – peak detector is executed by the microcontroller. This method originates by acquiring signal from the subject and necessary pre-processing is carried out on the signal in order to achieve the denoised signal. Subsequently, this filtered signal is handed over to microcontroller where a pulse is generated for each R – peak that is found in the QRS complex of ECG signal. The microcontroller is embedded with a signal processing algorithm. The algorithm used to determine the R – peaks is double differentiation method which is straightforward and robust.